Management of various clinical forms of leukoplakia with diode laser therapy -follow up of 5 cases - Dr..Ruchi Bhuyan,Dr. Basant Choudhary (International Journal of Advanced Science and Technology, 2020)
Objective: To study the application of diode laser in the treatment of oral leukoplakia. Materials & methods: In this study we considered 5 case reports those were having oral leukoplakia which was confirmed by biopsy test and treated with diode laser. Results: Diode laser provides painless and an early healing of wound that produced by the surgery. Healing time period was in between 7th days to 30th days after the laser treatment and there is no recurrence in between 2 year follow up the study. Conclusions: Diode laser is an effective treatment option to removing the infected tissues in the management of oral leukoplakia and also helpful to prevents malignancy.